Guidelines on: COVID-19 Vaccine Induced Thrombosis, Bleeding, and Thrombocytopenia - Morais, Sara (2021)
After widespread vaccination with COVID-19 vaccines, there have been worldwide reports on thrombosis, bleeding, and thrombocytopenia. Recently, a rare syndrome with a high mortality rate consisting of an unusual combination of thrombocytopenia and thrombosis, in particular cerebral venous sinus thrombosis, which clinically resembles heparin-induced thrombocytopenia, was reported following vaccination. Different statements and recommendations were developed regarding the definition, diagnosis, and treatment of these rare complications. We present here a protocol with recommendations, based on current evidence.